The Role of Custom Risk-Specific HSSEQ Software Solutions in Preventing Human Error and Safety System Bypass for Process Safety and Risk Mitigation in Heavy Industries - Bahar, Zeynep; Duygu Bilgen, Havva; Orcun , Sarioguz (International Journal of Scientific Research and Management (IJSRM), 2025)
It is always acknowledged that industrial accidents usually happen due to human error, and estimates quote almost 80 per cent of accidents happening due to operator, a hole in the procedure or system bypassing. These mistakes not only undermine the safety of the workers but also cause huge economic losses, harm the environment, and tarnish the reputation. Conventional safety management systems that rely profoundly on monitoring safety compliance checklists and reactive measures have failed to respond adequately to the potential of current industrial risks.This paper presents a case study of the importance of custom, risk-specific health, safety, security, environment, and quality (HSSEQ) software solutions in reducing the occurrence of human error and avoiding the bypass of safety systems. Based on the principles of human factors engineering and inherently safer design, the solutions combine real-time monitoring, multi-channel alert and notification, AI-driven hazard detection, digital permit-to-work (PTW) systems, and automated compliance reporting into one integrated platform. Such systems can provide multiple lines of defence, using predictive analytics and scenario-based safety validations, and automating procedures, to minimise the possibility of operational errors growing into accidents.The evaluations will be performed based on the synthesis of empirical reports, case scenarios in the industry, and technical specifications, including core basics of the components, integration planning with legacy infrastructure, regulatory conformance architecture, training, and implementation models. Results show that the organizations that introduce such systems report as much as a 30 percent decline in accidents at workplaces, an 82 percent increase in retention rates of employees due to an increase in safety culture, and vast savings in costs, attaining an average of $2.00 on the dollar spent on safety schemes. In addition, the feature of safety data centralization, predictive risk detection, and ensuring that businesses will always comply with safety standards like OSHA, ISO 14001, and ISO 45001, ensures that the software will be a deciding element in enhancing industrial safety performance.